Evaluation of four vegetable peelings as meat tenderizers - Zaragosa, Eufrocinia M.; De Leon, Sonia Y. (1964.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetables